Liver organoid as a 3D in vitro model for drug validation and toxicity assessment. (July 2021) - Brooks, Anastasia; Liang, Xiaowen; Zhang, Yonglong; Zhao, Chun-Xia; Roberts, Michael S.; Wang, Haolu; Zhang, Lei; Crawford, Darrell H.G.
Abstract: The past decade has seen many advancements in the development of three-dimensional (3D) in vitro models in pharmaceutical sciences and industry. Specifically, organoids present a self-organising, self-renewing and more physiologically relevant model than conventional two-dimensional (2D) cell cultures. Liver organoids have been developed from a variety of cell sources, including stem cells, cell lines and primary cells. They have potential for modelling patient-specific disease and establishing personalised therapeutic approaches. Additionally, liver organoids have been used to test drug efficacy and toxicity. Herein we summarise cell sources for generating liver organoids, the advantages and limitations of each cell type, as well as the application of the organoids in modelling liver diseases. We focus on the use of liver organoids as tools for drug validation and toxicity assessment. Graphical Abstract: ga1